The Choreographic Concept of Hasta Sawanda in the "Jepin Laba-laba Dance" of Mempawah Malay Cultural Tradition - Aditya, Mega Cantik Putri (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
The classification of dance in Indonesia has many kinds, ranging from the form of dance, the origin of the formation of dance to the function of dance in social life. In addition, choreographic concepts related to dance attitudes have also emerged from researchers and traditional dance practitioners, one of which is the concept of hasta sawanda. The concept of hasta sawanda includes pacak, pancat, caterpillar, lulut, luwes, wiled, wirama, and gending. Malay tradition has one of the dances, Jepin Laba-laba Dance, which requires cohesiveness and complexity in the use of its properties. Jepin Laba-laba dance is inspired by spiders making their nests but this dance does not have a story (non-literary), the spider animal is only a reference and reference for making its movements. Descriptive method and data presentation in this study aims to describe the concept of hasta sawanda in Jepin Laba-laba Dance. The results of the analysis can be concluded and found that, there are elements of dance presentation that are directly related to the concept of hasta sawanda. Awareness of the attitude and also the process of exploring a dance is very influential on the appearance of dancers when on stage.